Immediate management of maxillo-mandibular trauma. Case presentation - Alain Soto Ugalde (Medisur)
Facial fractures are rare in children, for that reason the case of a 10-year-old girl is presented. She is a mestizo, urban origin, with a history of health who after a fall of approximately 2.5 m in height, suffered a severe anterior and inferior anterior dentoalveolar trauma causing a dentoalveolar fracture in the anterior superior sector from 12 to 22, dislocation of 12, 11 and 22 and avulsion of 21 (which could be recovered at the site of the trauma) and dentoalveolar fracture in the anteroinferior sector from 32 to 42. The case was received at the emergency department of the Pediatric Hospital Paquito González Cueto University and attended in the Maxillofacial Surgery room. Surgical treatment for soft tissue wounds was performed by suturing, reducing and stabilizing the fracture in the anterior superior sector by means of Erich's splint and in the anteroinferior sector by means of osteosynthesis with wire in figure-eight. Twenty first was reimplanted and fixed to the splint by osteosynthesis with wire. Treatment with soft and liquid diet, analgesics, antibiotic therapy, thermotherapy and warm mouth rinse with saline solution was indicated. The splint was maintained for 21 days, managing to consolidate the fractures and 21 in its socket. It was possible to reimplant the avulsed tooth avoiding the aesthetic, functional and psychic consequences of trauma; the girl rejoined society.